Faktor Faktor yang Mempengaruhi Purchase Intention Codashop pada Generasi Z di Kota Depok - Fathannaufal Amiludin; Diena Noviarini; Meta Bara Berutu (Indo Publishing, 2026)
This study aims to analyze the effects of perceived ease of use, perceived usefulness, perceived playfulness, and attitude on purchase intention toward Codashop top-up services among Generation Z in Depok. This research employed a quantitative approach using a survey method. The population consisted of Generation Z in Depok who had used Codashop at least once. The sample was selected using purposive sampling, resulting in 198 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that perceived ease of use and perceived playfulness have a positive and significant effect on purchase intention. Meanwhile, perceived usefulness and attitude do not have a significant effect on purchase intention. The R-square value of 0.308 indicates that the four independent variables explain 30.8% of the variance in purchase intention, while the remaining variance is explained by other variables outside the model. This study contributes theoretically to digital consumer behavior research and practically to Codashop in improving user experience and marketing strategies for Generation Z.